PENGARUH PENDAPATAN NELAYAN TERHADAP PEMENUHAN KEBUTUHAN PENDIDIKAN ANAK DI WILAYAH PESISIR PANTAI - Fransiska Paramata; Framawati Dumulo; Yuliyanti Toralawe; Melizubaida Mahmud; Agil Bahsoan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The instability of fishermen's economic conditions in coastal areas often becomes a major obstacle to ensuring children's educational continuity. This associative quantitative research aims to analyze the effect of fishermen's income on fulfilling children's educational needs in Katialada Village, Kwandang District, North Gorontalo Regency. The study sample includes 103 fishermen families with school-age children determined using purposive sampling. Data were collected via structured questionnaires and analyzed using simple linear regression, t-tests, and coefficient of determination. Results show that fishermen's income has a positive and significant effect on fulfilling children's educational needs (Y ˆ=8.693+0.514X;t_